Method for preparing quartz from organic silicon
By performing plasma treatment and heat treatment on the silicone source, the problems of high cost, complex process and environmental pollution in the existing high-purity quartz manufacturing technology are solved, and the preparation and performance of high-purity quartz are improved, meeting the needs of the semiconductor industry.
Patent Information
- Application Number
- CN202411973436.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-18
AI Technical Summary
The existing high-purity quartz manufacturing technology has problems such as high cost, complex process, environmental pollution risks and product performance, which is particularly difficult to meet the semiconductor industry's demand for high-purity quartz.
High-purity quartz is prepared by plasma treatment and heat treatment using organic silicon sources such as ethyl orthosilicate (TEOS) or methyl orthosilicate (TMOS). The method includes plasma treatment of the silicone source, generating a precursor, and then heat treatment under high temperature conditions, removing impurities and increasing the purity of the quartz.
The preparation of high-purity quartz has been realized, which reduces production costs, simplifies the process flow, reduces the risk of environmental pollution, and improves the performance of quartz, which can meet the semiconductor industry's demand for high-purity quartz.
Smart Images

Figure CN119841538A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-purity quartz manufacturing, and in particular to a method for preparing quartz using organic silicon. Background Art
[0002] High-purity synthetic quartz sand has excellent physical and chemical properties and extremely high purity. It is widely used in photovoltaics, aviation, semiconductors, optical fibers and other fields. High-purity quartz has the advantages of high temperature resistance, corrosion resistance, high hardness, and good stability and electrical properties under high temperature and high pressure. Therefore, it is an important industrial raw material for high-end industries. In the semiconductor field, extremely high purity can effectively avoid the contamination of semiconductor components by impurities, thereby improving the performance and reliability of the device. High-purity quartz glass is widely used in crucibles, pipes, bell jars and quartz glass substrates in semiconductor production. With the development of integrated circuits, the semiconductor industry's requirements for quartz purity are also constantly increasing. At present, traditional high-purity quartz is mainly obtained by purifying natural quartz, but the purity of natural quartz sand is limited (99.9992%, 5N2), and the purity of the purified product is difficult to meet the requirements of the electronic grade polysilicon field.
[0003] At present, sol-gel method or gas phase synthesis of quartz is commonly used. The sol-gel method has a complex synthesis process and requires precise control of parameters such as pH, temperature, and solvent ratio; the organic solvents used in the synthesis process need to be recovered and treated, which poses a risk of environmental pollution; at the same time, the prepared synthetic quartz products contain a large number of bubbles, which have a great impact on product performance. The traditional gas phase synthesis method usually uses silicon tetrachloride as a raw material, which is gasified and then allowed to enter the reaction chamber to be heated and hydrolyzed by hydrogen and oxygen flames to prepare high-purity quartz. However, the hydrolysis time of silicon tetrachloride is extremely short, requiring the materials to be mixed evenly in a very short time; at the same time, the hydrolysis of silicon tetrachloride to generate HCl gas will cause corrosion to the reaction equipment. In order to ensure steady and safe production, traditional gas phase synthesis has more stringent requirements on equipment type, material, feed, heating method, etc., and the cost is relatively high.
[0004] Therefore, there is an urgent need to develop a method for preparing high-purity quartz from silicone with lower cost. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention provides a method for preparing quartz from organosilicon, the method of the present invention has low cost and the obtained quartz has high purity.
[0006] To this end, the first aspect of the present invention provides a method for preparing quartz from organic silicon, comprising the following steps:
[0007] Plasma-treating an organosilicon source to obtain a precursor;
[0008] Heat treating the precursor at 900-1500° C.
[0009] The gas source for the plasma treatment includes oxygen.
[0010] The present invention uses an organic silicon source as a raw material and adopts a plasma treatment and a heat treatment method to prepare quartz. Impurities are removed during the preparation process to improve the purity of the quartz. High-purity quartz has good chemical stability and inertness under high temperature and high pressure environments and can be used to prepare semiconductor-grade quartz crucible quartz sand or quartz glass.
[0011] In some embodiments of the present invention, the organosilicon source comprises a silicate.
[0012] In some embodiments of the present invention, the silicate includes tetraethyl orthosilicate (TEOS) and / or methyl orthosilicate (TMOS). The traditional gas phase synthesis method for preparing high-purity quartz sand mainly uses silicon tetrachloride as raw material, and the byproduct HCl will affect the service life of the reaction equipment, and the requirements for the material, heating method, etc. of the reaction equipment are more stringent. The byproducts of preparing high-purity quartz sand by gas phase synthesis using TEOS or TMOS as raw materials are CO2 and H2O, which is more environmentally friendly and energy-saving compared with the traditional hydrolysis of silicon tetrachloride. At the same time, plasma is generally neutral, which can avoid oxidation and reduction of materials. When heated, it can provide a purer reaction environment, which is conducive to the synthesis of high-purity quartz. In addition, using TEOS or TMOS as raw materials, high-purity quartz is prepared by plasma gas phase synthesis. Compared with the sol-gel method, the product has fewer bubbles inside the quartz and better performance of quartz sand.
[0013] Tetraethyl orthosilicate (TEOS) and methyl orthosilicate (TMOS) are common organosilicon compounds. They have similar physical properties and are both colorless, transparent liquids with good solubility and reactivity. They are soluble in organic solvents such as ethanol and propanol.
[0014] In some embodiments of the present invention, the flow rate of the oxygen is 0.5-10 L / min. Thus, the organic silicon source can be fully treated with plasma.
[0015] In some embodiments of the present invention, the gas source for the plasma treatment further comprises argon and / or nitrogen. Argon and / or nitrogen can be used as carrier gas, which can provide a suitable environment to excite oxygen to form plasma and help the active substances in the plasma to react with the organosilicon source.
[0016] In some embodiments of the present invention, the flow rate of the argon gas is 0.05-8 L / min, thereby further helping the oxygen to be excited.
[0017] In some embodiments of the present invention, the flow rate of the nitrogen gas is 0.05-8 L / min, thereby further helping the oxygen to be excited.
[0018] In some embodiments of the present invention, the plasma treatment is performed on a gaseous organosilicon source; the flow rate of the gaseous organosilicon source is 0.1-12 L / min.
[0019] In some embodiments of the present invention, the temperature of the plasma treatment is 1000-1300°C. Compared with the traditional oxyhydrogen flame, the plasma heating method for synthesizing quartz has the advantages of higher temperature and wider control range, concentrated energy distribution, high reaction purity, and more stable process. In addition, the energy of the plasma heat source is concentrated, and the heat can be highly concentrated in the reaction area, making the reaction more efficient and fast. This helps to improve the synthesis rate of quartz and the quality of the product and reduce energy waste. The energy distribution of the traditional oxyhydrogen flame is relatively dispersed, and in some reactions with high energy concentration requirements, it cannot achieve the desired effect. In addition, the generation and maintenance of plasma is relatively stable, not easily disturbed by external factors, and can ensure the continuous progress of the reaction process, thereby improving the stability of the process and the consistency of the product. The stability of the traditional oxyhydrogen flame may be affected by factors such as the supply pressure and flow rate of hydrogen and oxygen, and more precise control and adjustment are required to ensure the stability of the flame.
[0020] In some embodiments of the present invention, the plasma treatment time is 1-3 hours.
[0021] In some embodiments of the present invention, the heat treatment includes a first heat treatment and a second heat treatment performed sequentially; the temperature of the first heat treatment is 900-1400°C and the time is 8-36 hours; the temperature of the second heat treatment is 1200-1500°C and the time is 2-16 hours. The first heat treatment can remove the hydroxyl groups in the precursor, and the second heat treatment can make the quartz denser.
[0022] A second aspect of the present invention provides quartz prepared by the above method for preparing quartz using organosilicon.
[0023] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0025] Figure 1 An optical microscope image of high-purity synthetic quartz sand according to Example 1 of the present invention is shown;
[0026] Figure 2 A flow chart showing the preparation of quartz from organosilicon according to one embodiment of the present invention is shown;
[0027] Figure 3 A process diagram showing the preparation of quartz from organosilicon according to one embodiment of the present invention is shown;
[0028] Figure 4 The infrared spectra of the quartz obtained in Example 1 of the present invention before and after dehydroxylation are shown;
[0029] Figure 5 Optical microscope images of quartz obtained in Example 1 of the present invention and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0030] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0031] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0032] The first aspect of the present invention provides a method for preparing quartz from organic silicon, comprising the following steps:
[0033] Plasma-treating an organosilicon source to obtain a precursor;
[0034] Heat treating the precursor at 900-1500° C.
[0035] The gas source for the plasma treatment includes oxygen.
[0036] The present invention uses an organic silicon source as a raw material and adopts a plasma treatment and a heat treatment method to prepare quartz. Impurities are removed during the preparation process to improve the purity of the quartz. High-purity quartz has good chemical stability and inertness under high temperature and high pressure environments and can be used to prepare semiconductor-grade quartz crucible quartz sand or quartz glass.
[0037] The preparation process of the invention is simple, the conversion rate is high, the synthesis conditions are mild, and it is easy to produce on a large scale.
[0038] In some embodiments of the present invention, the organosilicon source comprises a silicate.
[0039] In some embodiments of the present invention, the silicate includes tetraethyl orthosilicate (TEOS) and / or methyl orthosilicate (TMOS). The traditional gas phase synthesis method for preparing high-purity quartz sand mainly uses silicon tetrachloride as raw material, and the byproduct HCl will affect the service life of the reaction equipment, and the requirements for the material, heating method, etc. of the reaction equipment are more stringent. The byproducts of preparing high-purity quartz sand by gas phase synthesis using TEOS or TMOS as raw materials are CO2 and H2O, which is more environmentally friendly and energy-saving compared with the traditional hydrolysis of silicon tetrachloride. At the same time, plasma is generally neutral, which can avoid oxidation and reduction of materials. When heated, it can provide a purer reaction environment, which is conducive to the synthesis of high-purity quartz. In addition, using TEOS or TMOS as raw materials, high-purity quartz is prepared by plasma gas phase synthesis. Compared with the sol-gel method, the product has fewer bubbles inside the quartz and better performance of quartz sand.
[0040] In some embodiments of the present invention, the purity of the organosilicon source is ≥ 99.9%.
[0041] In some embodiments of the present invention, the organosilicon source is vaporized before the plasma treatment, and the vaporization treatment includes vaporizing the organosilicon source at 170-200° C. The vaporized organosilicon source is more easily mixed with O2.
[0042] In some embodiments of the present invention, the vaporization temperature is 200-300°C.
[0043] In some embodiments of the present invention, the flow rate of the oxygen is 0.5-10 L / min. Thus, the organic silicon source can be fully plasma treated. As an example, the flow rate of the gaseous organic silicon source can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 12 L / min.
[0044] In some embodiments of the present invention, the gas source for the plasma treatment further comprises argon and / or nitrogen. Argon and / or nitrogen can be used as carrier gas, which can provide a suitable environment to enable oxygen to be excited at a high voltage to form plasma and help the active substances in the plasma to react with the organosilicon source.
[0045] In some embodiments of the present invention, the flow rate of the argon gas is 0.05-8 L / min. Thus, the oxygen can be further stimulated. As an example, the flow rate of the argon gas can be 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7 or 8 L / min.
[0046] In some embodiments of the present invention, the flow rate of the nitrogen is 0.05-8 L / min. Thus, the oxygen can be further stimulated. As an example, the flow rate of the nitrogen can be 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7 or 8 L / min.
[0047] In some embodiments of the present invention, the plasma treatment is performed on a gaseous organosilicon source; the flow rate of the gaseous organosilicon source is 0.1-12 L / min. As an example, the flow rate of the gaseous organosilicon source can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 L / min.
[0048] In some embodiments of the present invention, the temperature of the plasma treatment is 1000-1300°C. Compared with the traditional oxyhydrogen flame, the plasma has the advantages of higher temperature and wider control range, concentrated energy distribution, high reaction purity, and more stable process when synthesizing quartz by plasma heating. In addition, the energy of the plasma heat source is concentrated, and the heat can be highly concentrated in the reaction area, making the reaction more efficient and fast. This helps to improve the synthesis rate of quartz and the quality of the product and reduce energy waste. The energy distribution of the traditional oxyhydrogen flame is relatively dispersed, and in some reactions with high energy concentration requirements, it cannot achieve the desired effect. In addition, the generation and maintenance of plasma are relatively stable, not easily disturbed by external factors, and can ensure the continuous progress of the reaction process, thereby improving the stability of the process and the consistency of the product. The stability of the traditional oxyhydrogen flame may be affected by factors such as the supply pressure and flow rate of hydrogen and oxygen, and more precise control and adjustment are required to ensure the stability of the flame. As an example, the temperature of the plasma treatment can be 1000, 1100, 1200 or 1300°C.
[0049] In some embodiments of the present invention, the plasma treatment time is 1-3 hours. As an example, the plasma treatment time can be 1, 1.5, 2, 2.5 or 3 hours.
[0050] In some embodiments of the present invention, the reaction equation involved in the plasma treatment process is as follows:
[0051] Si(OCH3)4+O2→SiO2+CO2+H2O (1)
[0052] Si(OC2H5)4+O2→SiO2+CO2+H2O (2)
[0053] In some embodiments of the present invention, the precursor is dried before the heat treatment; the drying is performed in an inert atmosphere.
[0054] In some embodiments of the present invention, the drying temperature is 100-300° C. and the drying time is 1-4 h.
[0055] In some embodiments of the present invention, the heat treatment time is 10-40 hours.
[0056] In some embodiments of the present invention, the heating rate of the heat treatment is 1-2°C / min.
[0057] In some embodiments of the present invention, the heat treatment includes a first heat treatment and a second heat treatment performed sequentially; the temperature of the first heat treatment is 900-1400°C and the time is 8-36 hours; the temperature of the second heat treatment is 1200-1500°C and the time is 2-16 hours. The first heat treatment can remove the hydroxyl groups in the precursor, and the second heat treatment can make the quartz denser.
[0058] In some embodiments of the present invention, the method of preparing quartz from organosilicon, such as Figure 2 , Figure 3 As shown, the following steps are included:
[0059] Step 1: Place the organosilicon source in a steam generator for vaporization.
[0060] In some embodiments of the present invention, the organosilicon source is TEOS and TMOS.
[0061] In some embodiments of the present invention, the purity of the organic silicon sources TEOS and TMOS is ≥99.99%, and the temperature range of the steam generator is controlled at 170-200°C.
[0062] Step 2: The vaporized TEOS or TMOS is introduced into the innermost sleeve, the working gas is introduced into the middle sleeve, the cooling gas is passed into the outer sleeve, a high-frequency coil is wrapped around the outside of the sleeve, and the raw gas and the working gas are mixed and then enter the plasma reaction zone to react by being heated by the plasma flame.
[0063] In some embodiments of the present invention, TEOS and TMOS gases are transported to the reaction chamber by a carrier gas.
[0064] In some embodiments of the present invention, O2 or air is used as the working gas of the plasma, and the flow rate of the working gas is controlled at 0.5-9.5 L / min; the gas flow rate of TEOS and TMOS is 0.1-12 L / min; nitrogen or argon is used as the carrier gas, and the flow rate is 0.05-1 L / min; argon, helium or nitrogen is used as the cooling gas, and the flow rate of the cooling gas is controlled at 0.1-8 L / min; the plasma reaction temperature is 1000-1300°C; a multi-layer quartz sleeve is used for the introduction pipeline, and the gas enters the plasma torch reaction zone from different sleeves; the carrier gas carries and transports the working gas into the reaction zone, and can form plasma after heating, but does not participate in the chemical reaction, and the cooling gas releases high temperature to burn the quartz sleeve.
[0065] Step 3: The gas-phase SiO2 particles after the reaction are settled in the sedimentation chamber and then captured by the particle collector. The particle collector is connected to the cartridge filter through a sealing sleeve, and the cartridge filter is used to separate the gas-phase SiO2 particles and the gas product to obtain the gas-phase SiO2 particles.
[0066] In some embodiments of the present invention, the gas is extracted from the cartridge filter using a vacuum pump, and the gas is subsequently subjected to tail gas treatment; the gas-phase SiO2 particles can be efficiently captured because they remain on the cartridge filter.
[0067] In some embodiments of the present invention, the particle collector and the cartridge filter are connected by a quartz sleeve, and the pipeline is wrapped with insulation material; the sedimentation chamber is welded with 316L stainless steel; the particle collector is modified from a vacuum cleaner to collect the settled gas-phase SiO2 particles and send them into the quartz sleeve; the cartridge filter uses a glue-free cartridge filter with an accuracy of 1 to 200 μm; the vacuum pump uses one of a rotary vane mechanical pump, an oil diffusion pump, and a turbomolecular pump.
[0068] Step 4: The captured gas phase SiO2 particles are washed with pure water, dried after washing, and pressed into blocks using a shaping machine after drying to obtain high purity quartz blocks. The drying operations in the above steps 1-3 and step 4 are all performed under the protection of inert gas.
[0069] In some embodiments of the present invention, the washed gas-phase SiO2 particles are washed 2 to 3 times with ultrapure water having a purity of ≥99.99%, the drying temperature is 100 to 300°C, and the drying time is 1 to 4 hours.
[0070] In some embodiments of the present invention, the shaping machine is selected from one of a mechanical briquetting machine, a spray granulator, and a powder blending machine, and the shaping machine extrude the gas-phase SiO2 particles into high-purity quartz blocks.
[0071] Step 5: Place the high-purity quartz block in a heating furnace for heating to remove hydroxyl groups in the high-purity quartz block. Continue to heat the block after dehydroxylation to densify the high-purity quartz block. Then use a crusher to crush and grind the high-purity quartz block to make high-purity quartz sand.
[0072] In some embodiments of the present invention, a high-purity quartz block is placed in a heating furnace bin, the dehydroxylation temperature is 900-1400°C, the insulation time is 8-36h, the heating rate is 2-10°C / min, and the temperature is continued to be increased after dehydroxylation to densify the quartz block, the temperature is maintained at 1200-1500°C, the insulation time is 2-16h, and a double-roll grinder is used to crush and grind the quartz block to produce high-purity quartz sand.
[0073] A second aspect of the present invention provides quartz prepared by the above method for preparing quartz using organosilicon.
[0074] In some embodiments of the present invention, the impurity content of the quartz is less than 1 ppm.
[0075] In some embodiments of the present invention, the purity of the quartz is ≥99.9999%. High-purity quartz has good chemical stability and inertness under high temperature and high pressure environments.
[0076] In some embodiments of the present invention, the density of the quartz is 1.0-1.2 g / cm 3 .
[0077] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.
[0078] Example 1
[0079] The method for preparing quartz from organosilicon in this embodiment specifically comprises the following steps:
[0080] Step 1: First, high-purity tetraethyl orthosilicate (TEOS) with a purity of ≥99.99% is used as a raw material, and TEOS is added into a steam generator in an amount of 2 / 3 of the volume of the steam generator. The temperature of the steam generator is maintained at 200°C to vaporize TEOS, and material is added intermittently to keep the liquid content in the steam generator not less than 1 / 3 of the volume.
[0081] Step 2: Use nitrogen as carrier gas to transport TEOS gas from the central sleeve into the reaction zone, the working gas O2 enters the reaction zone along the middle sleeve, and the cooling gas argon enters the reaction zone along the outer sleeve, and ignites the plasma flame for reaction, wherein the TEOS flow rate is 0.5L / min, the nitrogen flow rate is 0.2L / min, the O2 flow rate is 1.5L / min, the argon flow rate is 1.8L / min, the reaction temperature is 1200℃, and the time is 2h.
[0082] Step 3: The product obtained in step 2 is collected by a particle collector after settling in a settling chamber, and then enters a non-glue cartridge filter along a sealing sleeve. An oil diffusion pump is used to extract the gas from the cartridge filter for subsequent exhaust gas treatment; the gas-phase SiO2 particles are captured in the cartridge filter.
[0083] Step 4: Wash the gas-phase SiO2 particles twice with ultrapure water, and then dry them in a nitrogen atmosphere for 2 hours, controlling the temperature at 200°C; press the dried gas-phase SiO2 particles into quartz blocks using a mechanical briquetting machine; collect the gas-phase SiO2 particles and put them into a clean box, rinse them with high-purity water, and the clean box is made of PFA plastic.
[0084] Step 5: Place the quartz block in a heating furnace, heat it to 1000°C at a heating rate of 2°C / min, and keep the temperature constant for 12 hours to remove the hydroxyl groups in the quartz block. After the removal of hydroxyl groups, continue to heat it to 1350°C and keep the temperature constant for 4 hours to obtain a more compact high-purity quartz block. Use a roller grinder to crush and grind the high-purity quartz block to make high-purity quartz sand. The optical microscope image of the quartz in this embodiment is as follows: Figure 1 and Figure 5 The element detection results of the high-purity synthetic quartz sand of this embodiment are shown in Table 1.
[0085] The heating temperature in the above step 5 is adjusted to 1200°C for dehydroxylation; infrared testing is performed on the product before dehydroxylation (the product obtained in step 4), the high-purity quartz obtained in the above step 5, and the quartz dehydroxylated at 1200°C. The infrared spectra are shown in FIG. Figure 4 As shown by Figure 4 It can be seen that the infrared absorption peak of hydroxyl is usually located at 3000-3700cm -1 The wave number range is called OH stretching vibration. It can be seen from the figure that with the increase of dehydroxylation temperature, the intensity of the hydroxyl absorption peak decreases significantly, and the dehydroxylation effect is obvious.
[0086] Table 1
[0087]
[0088] Example 2
[0089] The method for preparing quartz from organosilicon in this embodiment specifically comprises the following steps:
[0090] Step 1: First, high-purity methyl orthosilicate (TMOS) with a purity of ≥99.99% is used as a raw material, and TMOS is added into a steam generator in an amount of 2 / 3 of the volume of the steam generator. The temperature of the steam generator is maintained at 200° C. to vaporize TMOS and intermittently add material to keep the liquid content in the steam generator not less than 1 / 3 of the volume.
[0091] Step 2: Use argon as carrier gas to transport TMOS gas from the central sleeve into the reaction zone, the working gas O2 enters the reaction zone along the middle sleeve, and the cooling gas argon enters the reaction zone along the outer sleeve, and ignites the plasma flame for reaction, wherein the TMOS flow rate is 0.57 L / min, the argon (carrier gas) flow rate is 0.25 L / min, the O2 flow rate is 1.7 L / min, the argon (cooling gas) flow rate is 1.9 L / min, the reaction temperature is 1250°C, and the time is 2.5 h.
[0092] Step 3: The products generated by the reaction are collected by the particle collector after settling in the sedimentation chamber, and enter the non-glue cartridge filter along the sealing sleeve. The gas is extracted from the cartridge filter using an oil diffusion pump, and the gas-phase SiO2 particles are captured in the cartridge filter.
[0093] Step 4: Wash the gas-phase SiO2 particles twice with ultrapure water, and then dry them in a nitrogen atmosphere for 2.5 hours, controlling the temperature at 220°C; extrude the dried gas-phase SiO2 particles into quartz blocks using a spray granulator; wherein, the gas-phase SiO2 particles are collected and placed in a clean box, and rinsed with high-purity water. The clean box is made of PFA plastic.
[0094] Step 5: Place the quartz block in a heating furnace, heat it to 1100°C at a heating rate of 3°C / min, and maintain the constant temperature for 16 hours to remove the hydroxyl groups in the quartz block. After the dehydroxylation is completed, continue to heat it to 1400°C and maintain the constant temperature for 3.5 hours to obtain a more compact high-purity quartz block. Use a double-roll grinder to crush and grind the high-purity quartz block to make high-purity quartz sand.
[0095] The test results of the high-purity synthetic quartz sand of this embodiment are shown in Table 2.
[0096] Table 2
[0097]
[0098] Example 3
[0099] The method for preparing quartz from organosilicon in this embodiment specifically comprises the following steps:
[0100] Step 1: First, high-purity tetraethyl orthosilicate (TEOS) with a purity of ≥99.99% and methyl orthosilicate (TMOS) are mixed in a ratio of 1:1 to prepare a mixed raw material, which is added to a steam generator in an amount of 2 / 3 of the volume of the steam generator. The temperature of the steam generator is maintained at 200°C to vaporize the mixed raw material and intermittently add material to keep the liquid content in the steam generator not less than 1 / 3 of the volume.
[0101] Step 2: Use argon as carrier gas to transport TEOS and TMOS gases from the central sleeve into the reaction zone, the working gas O2 enters the reaction zone along the middle sleeve, and the cooling gas nitrogen enters the reaction zone along the outer sleeve, igniting the plasma flame for reaction, wherein the mixed gas flow rate is 0.52 L / min, the argon flow rate is 0.21 L / min, the O2 flow rate is 1.78 L / min, the nitrogen flow rate is 1.6 L / min, the reaction temperature is 1270°C, and the time is 2 hours.
[0102] Step 3: The product obtained in step 2 is collected by a particle collector after settling in a settling chamber, and enters a non-glue cartridge filter along a sealing sleeve. An oil diffusion pump is used to extract the gas from the cartridge filter for subsequent exhaust gas treatment; gas-phase SiO2 particles are captured in the cartridge filter.
[0103] Step 4: Wash the gas-phase SiO2 particles twice with ultrapure water, and then dry them in a nitrogen atmosphere for 3 hours, controlling the temperature at 225°C; extrude the dried gas-phase SiO2 particles into block structures using a powder blender; wherein, the gas-phase SiO2 particles are collected and placed in a clean box, and rinsed with high-purity water. The clean box is made of PFA plastic.
[0104] Step 5: Place the quartz block in a heating furnace, heat it to 1200°C at a heating rate of 2.5°C / min, and maintain the constant temperature for 10 hours to remove the hydroxyl groups in the quartz block. After the dehydroxylation is completed, continue to heat it to 1450°C and maintain the constant temperature for 3 hours to obtain a more compact high-purity quartz block. Use a double-roll grinder to crush and grind the high-purity quartz block to make high-purity quartz sand.
[0105] The test results of the high-purity synthetic quartz sand of this embodiment are shown in Table 3.
[0106] Table 3
[0107]
[0108] After dehydroxylation and densification, the packing density of the quartz block of this embodiment changes as shown in Table 4.
[0109] Table 4
[0110]
[0111] Comparative Example 1
[0112] In this comparative example, TEOS is used as a raw material and a sol-gel method is used to prepare high-purity synthetic quartz. The specific steps are as follows:
[0113] Step 1: Take appropriate amounts of TEOS, organic alcohol compound and deionized water into a reactor, add a catalyst, and stir at 60° C. for 2 hours, wherein the mass ratio of TEOS: organic alcohol compound: deionized water is 7:5:1.
[0114] Step 2: After reacting for 2 hours, add deionized water with a mass of 2.5 times that of TEOS into the reactor, and continue stirring and reacting for 8 hours until the liquid turns into a sol state.
[0115] Step 3: Place the sol obtained by the reaction in a drying oven and dry for 12 hours. After taking it out, add an appropriate amount of HCl solution and acid wash it under the action of ultrasound for 0.5 hours.
[0116] Step 4: The acid-washed sol was transferred to a drying oven for drying, and then the gel was placed in a muffle furnace and calcined at 1200°C for 16 hours to obtain high-purity synthetic quartz sand. The optical microscope image of the quartz sand is shown in the figure. Figure 5 As shown, it can be seen that compared with Example 1, there are more bubbles in Comparative Example 1.
[0117] The test results of high-purity synthetic quartz sand are shown in Table 5:
[0118] Table 5
[0119]
[0120] Comparative Example 2
[0121] In this comparative example, TMOS was used as a raw material and a sol-gel method was used to prepare high-purity synthetic quartz. The specific steps are as follows:
[0122] Step 1: Take appropriate amounts of TMOS, organic alcohol compound and deionized water into a reactor, add a catalyst, and stir at 65° C. for 2.5 hours, wherein the mass ratio of TMOS: organic alcohol compound: deionized water is 7.5:4.7:1.
[0123] Step 2: After reacting for 2 h, add deionized water with a mass of 2.5 times that of TMOS into the reactor, and continue stirring and reacting for 9 h until the liquid turns into a sol state.
[0124] Step 3: Place the sol obtained by the reaction in a drying oven and dry for 16 hours. After taking it out, add an appropriate amount of HCl solution and acid wash it under the action of ultrasound for 0.5 hours.
[0125] Step 4: The acid-washed sol is transferred to a drying oven for drying, and then the gel is placed in a muffle furnace and calcined at 1250°C for 16 hours to obtain high-purity synthetic quartz sand.
[0126] Among them, the test results of high-purity synthetic quartz sand are shown in Table 6:
[0127] Table 6
[0128]
[0129] Comparative Example 3
[0130] In this comparative example, SiCl4 was used as a raw material and a gas phase synthesis method was adopted to prepare high-purity synthetic quartz.
[0131] Step 1: First, a high-purity SiCl4 solution with a purity of ≥99.99% is added to a steam generator for vaporization.
[0132] Step 2: Use nitrogen as a carrier gas to transport gas from the central sleeve into the reaction chamber, and enter the reaction chamber along the outer sleeve with a molar ratio of H2 to O2 of 1:2.75, ignite the hydrogen-oxygen flame for reaction, wherein the SiCl4 flow rate is 0.68 L / min, the nitrogen flow rate is 0.21 L / min, the hydrogen-oxygen mixed gas flow rate is 1.8 L / min, and the reaction temperature is 1280°C.
[0133] Step 3: The products generated by the reaction enter the non-gel cartridge filter along the sealing sleeve, and the gas is extracted from the cartridge filter using an oil diffusion pump, and the quartz sand particles are captured in the cartridge filter.
[0134] Step 4: Wash the quartz sand particles twice with ultrapure water, and then dry them in a nitrogen atmosphere for 2.5 hours, controlling the temperature at 210°C; place the dried quartz sand in a rotary heating furnace for roasting, maintain the roasting temperature at 1270°C for 20 hours in a nitrogen atmosphere, and obtain high-purity synthetic quartz sand after cooling.
[0135] Among them, the test results of high-purity synthetic quartz sand are shown in Table 7:
[0136] Table 7
[0137]
[0138] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0139] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing quartz from organosilicon, characterized in that: The following steps are involved: Plasma-treating an organosilicon source to obtain a precursor; Heat treating the precursor at 900-1500° C. The gas source for the plasma treatment includes oxygen.
2. The method for preparing quartz from organosilicon according to claim 1, characterized in that: The organosilicon source includes silicate.
3. The method for preparing quartz from organosilicon according to claim 2, characterized in that: The silicate includes ethyl orthosilicate and / or methyl orthosilicate.
4. The method for preparing quartz from organosilicon according to claim 1, characterized in that: The flow rate of the oxygen is 0.5-10 L / min.
5. The method for preparing quartz from organosilicon according to claim 1, characterized in that: The temperature of the plasma treatment is 1000-1300°C.
6. The method for preparing quartz from organosilicon according to claim 1, characterized in that: The gas source for the plasma treatment further comprises argon and / or nitrogen.
7. The method for preparing quartz from organosilicon according to claim 6, characterized in that: The flow rate of the argon gas is 0.05-8 L / min; and / or, The flow rate of the nitrogen is 0.05-8 L / min.
8. The method for preparing quartz from organosilicon according to claim 1, characterized in that: subjecting a gaseous organosilicon source to the plasma treatment; The flow rate of the gaseous organic silicon source is 0.1-12 L / min.
9. The method for preparing quartz from organosilicon according to claim 1, characterized in that: The heat treatment includes a first heat treatment and a second heat treatment performed sequentially; The temperature of the first heat treatment is 900-1400°C and the time is 8-36h; The temperature of the second heat treatment is 1200-1500° C., and the time is 2-16 hours.
10. Quartz obtained by the method for preparing quartz from organosilicon according to any one of claims 1 to 9.